Endoscopic ultrasound-guided placement of coils and cyanoacrylate embolization in refractory gastric variceal bleeding: a pediatric case report - Olmos, Juan I.; Oleas, Roberto; Alcívar, Juan A.; Baquerizo-Burgos, Jorge; Robles-Medranda, Carlos (Endoscopy International Open, 2019)
Background and study aims Gastric variceal bleeding management is challenging, especially in the pediatric population. Endoscopic cyanoacrylate glue injection is considered the standard for management of gastric varices but it is associated with a high rebleeding rate. Endoscopic ultrasound (EUS)-guided placement of coils with cyanoacrylate is a newly available technique with a lower rebleeding rate but there are no reported cases using this technique in pediatric patients. We report on a 12-year-old child with liver cirrhosis and gastric variceal hemorrhage who was refractory to the endoscopic cyanoacrylate injection and in whom hemostasis was achieved without rebleeding following EUS-guided coiling and cyanoacrylate injection. Neither rebleeding nor varix reappearance was noted on 12-month follow-up. EUS-guided coiling and cyanoacrylate injection is safe and feasible in pediatric patients and could be considered as rescue therapy for treatment of refractory gastric variceal bleeding.